Wątki hiszpańskie w twórczości Wawrzyńca Korwina (1465–1527) - Zawadzki, Robert K. (Collectanea Philologica, 2022)
In the article Robert K. Zawadzki relates how Wawrzyniec Korwin, a little – known Old – Polish writer described the Iberian peninsula in his astronomical treatise Cosmographia dans manuductionem in tabulas Ptolemaei. This author produced a specific picture of Spain that shared affinity with the Roman and Greek writers’ literary manner of writing about this country. The ancient literature had tended to see Spain as a land of prosperity and a district in which gold could be found as a mineral in the rivers. Korwin adopted this view of Spain. A separate section of Spanish threads in his dissertation are the Roman writers from the Iberian peninsula. The Polish author evokes the figure of Seneca and Lucan to quote fragments of the most important works of these writers. Bringing together Korwin’s remarks and ancient texts which he uses, RKZ demonstrates that the Korwin’s description of Spain although seen by some as an anachronism achieved its aim, it persuaded audiences of the magnificence of Spain.